Erosion behavior of Y2O3 in fluorine‐based etching plasmas: Orientation dependency and reaction layer formation. Issue 3 (26th November 2020) - Kindelmann, Moritz; Stamminger, Mark; Schön, Nino; Rasinski, Marcin; Eichel, Rüdiger‐A.; Hausen, Florian; Bram, Martin; Guillon, Olivier
Abstract: Even though advanced ceramics are widely applied as consumables in semiconductor etching processes, the erosion mechanisms and connected surface phenomena are not fully understood. Through the interaction with reactive species and ion bombardment during the plasma exposure, oxide ceramic materials like Y2 O3 are eroded by a physicochemical mechanism. In this study, fundamental phenomena of surface‐plasma interactions were investigated directly at the surface as well as in the near‐surface region after exposure to fluorine‐based etching plasmas. A straightforward re‐localization technique was used to investigate the microstructural features before and after the plasma exposure for up to 2 hours. Electron microscopy methods (scanning electron microscopy, electron backscatter diffraction) were coupled with atomic force microscopy, secondary ion mass spectroscopy, and transmission electron microscopy to study the surface topography and the corresponding reaction layer. Direct correlation of the microstructure before plasma exposure with the surface topography reveals a novel orientation‐dependent erosion mechanism that forms plateau‐like structures. Furthermore, the in‐depth analysis of the near‐surface area highlights the influence of the applied bias voltage on the physical damage and chemical gradient formation due to plasma exposure. The combined investigation of surface morphology and near‐surface properties reveals new fundamental aspects of the erosion behavior of polycrystalline yttria in CF4 ‐based etching plasmas. Abstract : Correlation of electron backscatter diffraction and atomic force microscopy measurements on plasma etched Y2 O3 revealed an orientation dependent erosion mechanism.